2021
DOI: 10.3390/w13131799
|View full text |Cite
|
Sign up to set email alerts
|

Measures to Cope with the Impact of Climate Change and Drought in the Island Region: A Study of the Water Literacy Awareness, Attitude, and Behavior of the Taiwanese Public

Abstract: This study assessed people’s water literacy awareness, attitudes, and behaviors to iden-tify strategies for coping with drought and water scarcity. The data from 653 questionnaires were analyzed by statistical validation and using IBM SPSS 22 and IBM AMOS 26.0. The views of students, housewives, swimming pool owners, schoolteachers, and experts were collected and finally examined by multivariate validation analysis. People have a high level of water literacy and developed sufficient water-saving habits (4.60).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…On the other hand, Sammel (2014)'s water literacy programme for Australian primary school pupils improved students' understanding of water-related issues and shaped their attitudes toward water use and conservation. Depending on their age, education level, and prior exposure to water-related issues, students' knowledge, attitudes, and values about water literacy can differ (Yu et al, 2021). Students who have participated in water literacy education initiatives typically have a greater understanding of the value of water and how they may contribute to the preservation and sustainable management of water resources.…”
Section: Knowledge Attitude and Value Of Water Literacy Among Studentsmentioning
confidence: 99%
“…On the other hand, Sammel (2014)'s water literacy programme for Australian primary school pupils improved students' understanding of water-related issues and shaped their attitudes toward water use and conservation. Depending on their age, education level, and prior exposure to water-related issues, students' knowledge, attitudes, and values about water literacy can differ (Yu et al, 2021). Students who have participated in water literacy education initiatives typically have a greater understanding of the value of water and how they may contribute to the preservation and sustainable management of water resources.…”
Section: Knowledge Attitude and Value Of Water Literacy Among Studentsmentioning
confidence: 99%
“…This might be related to the sanitation conditions in Taiwan. A study in Taiwan revealed that local inhabitants have good water management, water literacy awareness, and behavior, and as well as proper knowledge regarding to drinking water safety and hygiene [44].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…At the household level, one strategy to promote sustainable consumption could be to encourage water responsibility among users through practices such as paying attention to time spent bathing, cleaning water towers regularly and increasing awareness about tap and bottled water consumption (Yu and others, 2021). To this end, the island's water authority has been implementing strategies to enforce water resource protection, encouraging water saving behaviours and the use of products with water-saving labels while increasing water education among users (Wang and others, 2019).…”
Section: Consume Sustainablymentioning
confidence: 99%